Analysing the Environmental Consequences of Economic Dynamics: Oil Rents, Economic Growth, and Foreign Direct Investment on CO2 Emissions in OPEC Countries - Camila, Elmira Mufliha; Grisvia Agustin; Hadi Sumarsono (Profesional Muda Cendekia Publishing, 2024)
of economic activities in OPEC countries by examining how oil rents, economic growth, and foreign direct investment (FDI) influence CO2 emissions. It seeks to understand the individual and combined effects of these factors on environmental outcomes. The study will investigate how revenue from oil production, the rate of economic growth, and the level of foreign investment contribute to carbon dioxide emissions. Additionally, the research aims to provide policy recommendations to help mitigate CO2 emissions in these countries while considering their economic dynamics. Design/methodology/approach: This research uses quantitative methods, which are methods designed to test theories, show relationships between variables, provide statistical descriptions, and interpret the results Research Findings: Based on the results of the research conducted on the effect of Oil Rents, Economic Growth, and Foreign Direct Investment on CO2 Emissions in OPEC countries, the conclusion is that the variables of Oil Rents, Economic Growth, and Foreign Direct Investment individually do not affect CO2 Emissions in OPEC countries. However, when considered simultaneously, the variables of Oil Rents, Economic Growth, and Foreign Direct Investment do affect CO2 Emissions in OPEC countries Theoretical Contribution/Originality: The implications of the results from this study can provide valuable insights for policymakers in OPEC countries on how to manage Oil Rents, foster sustainable economic growth, and attract environmentally friendly FDI. The urgency is to equip policymakers with the necessary information to design and implement policies that support the energy transition, reduce CO2 emissions, and improve long-term economic welfare